Mental health law: a comparison of compulsory hospital admission in Italy and the UK - Aguirre, Lucienne; Padovano, Martina; Scopetti, Matteo; La Russa, Raffaele; Manetti, Federico; D’Errico, Stefano; Frati, Paola; Fineschi, Vittorio (Frontiers in Public Health, 2023)
In Europe, the Mental Health Law legal framework has had several changes throughout the years to achieve and develop new reforms, better mental health care, and protect the human rights of the patients. The UK national data shows rising detention rates and the disproportionate use of the legal framework among people from black and minority ethnic groups. At the national level, compulsory admissions are lower in Italy; it also shows that it has increased in the last few years in both countries. The lack of ethnic national data, especially in Italy, limited the ability to understand compulsory admission, discrimination, and stigma in mental health. The present study aims to compare the legal framework of Mental health law and compulsory hospital admission in Italy and the UK. A review of each country's latest amendments to mental health law and the number of compulsory hospital admissions was conducted to understand the impact of changes in mental health care.